Amniotic Fluid Bacterial Colonization, Antibiotic Susceptibility, and Associated Factors Among Women With Premature Rupture of Membranes at Mbarara Regional Referral Hospital, Southwestern Uganda - Ainomugisha, Brenda; Migisha, Richard; Agaba, Collins; Tibaijuka, Leevan; Owaraganise, Asiphas; Muhumuza, Joy; Bazira, Joel; Kayondo, Musa; Ngonzi, Joseph (Cureus, 2024)
Background: Amniotic fluid bacterial colonization in premature rupture of membranes (PROM) is known to initiate labor and lead to postpartum endometritis and early-onset neonatal sepsis. We determined the prevalence and factors associated with amniotic fluid bacterial colonization, described bacterial isolates and examined antibiotic susceptibility patterns among women seeking care at Mbarara Regional Referral Hospital (MRRH) in southwestern Uganda. Methods: We conducted a cross-sectional study from December 21, 2020 to June 12, 2021. We consecutively enrolled women with PROM at ≥24 weeks of gestation and aseptically picked two endo-cervical swabs. Aerobic cultures were performed on blood, chocolate, MacConkey agars, and polymerase chain reaction on culture-negative samples. Antibiotic susceptibility was performed via the Kirby-Bauer disk diffusion and dilution method. Interviewer-administered questionnaires were used to obtain participants’ sociodemographic, medical, and obstetric characteristics. We performed multivariable logistic regression to determine factors associated with bacterial colonization. Results: We enrolled 144 participants with a mean age of 26.5±6.2 years. The prevalence of cervical amniotic bacterial colonization was 35.4% (n=51; 95% confidence interval (CI): 28.0-43.7). Six bacteria were isolated: Klebsiella pneumoniae, Staphylococcus aureus, Enterobacter agglomerans, Escherichia coli, Streptococcus spp., and Enterococcus faecalis. Ciprofloxacin exhibited the highest sensitivity (88.6%), followed by cefuroxime (75%), while all isolated bacteria demonstrated resistance to ampicillin. Factors independently associated with cervical amniotic fluid bacterial colonization were prime gravidity (aOR=2.69; 95%CI: 1.07-6.71, p=0.035), obesity (aOR=3.15; 95%CI: 1.10-9.11, p=0.024), and being referred-in (aOR=2.37; 95% CI: 1.04-5.3, p=0.038). Conclusion: Approximately one-third of the women had amniotic fluid bacterial colonization, and this was associated with being prime gravida, being obese, and being referred. The most common bacteria isolated was K. pneumoniae, followed by S. aureus. There was good sensitivity to quinolones and cephalosporins, and all bacterial isolates were resistant to ampicillin - the recommended first line of treatment for PROM by the Ministry of Health calls for revision of guidelines.
Keywords: Amniotic fluid; Antibiotic susceptibility; Bacterial colonization; Premature rupture of membranes; Uganda